A study of CDR3 loop dynamics reveals distinct mechanisms of peptide recognition by T‐cell receptors exhibiting different levels of cross‐reactivity. Issue 4 (8th November 2017) - Tsuchiya, Yuko; Namiuchi, Yoshiki; Wako, Hiroshi; Tsurui, Hiromichi
Summary: T‐cell receptors (TCRs) can productively interact with many different peptides bound within the MHC binding groove. This property varies with the level of cross‐reactivity of TCRs; some TCRs are particularly hyper cross‐reactive while others exhibit greater specificity. To elucidate the mechanism behind these differences, we studied five TCRs in complex with the same class II MHC (1A b )‐peptide (3K), that are known to exhibit different levels of cross‐reactivity. Although these complexes have similar binding affinities, the interface areas between the TCR and the peptide–MHC (pMHC) differ significantly. We investigated static and dynamic structural features of the TCR–pMHC complexes and of TCRs in a free state, as well as the relationship between binding affinity and interface area. It was found that the TCRs known to exhibit lower levels of cross‐reactivity bound to pMHC using an induced‐fitting mechanism, forming large and tight interfaces rich in specific hydrogen bonds. In contrast, TCRs known to exhibit high levels of cross‐reactivity used a more rigid binding mechanism where non‐specific π ‐interactions involving the bulky Trp residue in CDR3 β dominated. As entropy loss upon binding in these highly degenerate and rigid TCRs is smaller than that in less degenerate TCRs, they can better tolerate changes in residues distal from the major contacts with MHC‐bound peptide. Hence, our dynamics study revealed that differences in the peptide recognition mechanisms by TCRs appear to correlate with the levels of T‐cell cross‐reactivity. Abstract : Molecular dynamics simulations were performed for five T‐cell receptor (TCR) –peptide–MHC (pMHC) systems, where TCRs exhibiting different levels of cross‐reactivity recognize the same pMHC. The results showed that the TCRs exhibiting lower levels of cross‐reactivity bound to pMHC using an induced‐fitting mechanism, forming large, tight interfaces rich in specific hydrogen bonds. In contrast, TCRs exhibiting higher levels of cross‐reactivity formed small, loose interfaces by a more rigid and degenerate binding mechanism. As entropy losses upon binding are smaller than those in the lower cross‐reactive TCRs, some amount of non‐specific π‐interactions seem sufficient for stable pMHC binding in the hyper cross‐reactive TCRs.